Analisis Kualitas Pelayanan Publik di Indonesia: Studi Literatur terhadap Implementasi Prinsip Good Governance - Nursahriza Nursahriza (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to analyze the concept of modern governance in public service delivery using a descriptive qualitative approach through an extensive literature review. Modern governance is understood as a governance model that emphasizes collaboration, transparency, adaptability, and the involvement of multiple actors within policy networks. The data were collected from books, journal articles, international institutional documents, and previous research relevant to governance and public administration. The findings indicate that modern governance significantly contributes to improving public service effectiveness, particularly through digital innovation, data integration, and collaborative mechanisms between government institutions and citizens. Several case studies—such as public service innovations in Surabaya, Surakarta, and various village administrations—demonstrate that this model can accelerate service processes and enhance public satisfaction. However, the implementation of modern governance still faces challenges, including limited resources, rigid bureaucratic culture, low public participation, and the inconsistent application of good governance principles. This study concludes that modern governance holds substantial potential to strengthen the quality of public services in Indonesia, yet requires strong governmental commitment, technological readiness, and active community involvement to be effectively implemented.